GIST of Mesocolon: A Case Report - Malla, S; Rawal, SB; Giri, NK (Medical Journal of Shree Birendra Hospital, 2012)
Gastrointestinal Stromal Tumor (GIST) is a rare soft tissue tumor and a GIST arising from the mesocolon is even rarer and sparsely reported in the world literature. Herein we report one such case that we encountered in our clinical practice and review the literature on the management of such a rare case. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6448 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 37-39